Glycogen synthase kinase 3 promotes multicellular development over unicellular encystation in encysting Dictyostelia - Kawabe, Yoshinori (EvoDevo, 2018)
BACKGROUND: Glycogen synthase kinase 3 (GSK3) regulates many cell fate decisions in animal development. In multicellular structures of the group 4 dictyostelid Dictyostelium discoideum, GSK3 promotes spore over stalk-like differentiation. We investigated whether, similar to other sporulation-inducing genes such as cAMP-dependent protein kinase (PKA), this role of GSK3 is derived from an ancestral role in encystation of unicellular amoebas. RESULTS: We deleted GSK3 in Polysphondylium pallidum, a group 2 dictyostelid which has retained encystation as an alternative survival strategy. Loss of GSK3 inhibited cytokinesis of cells in suspension, as also occurs in D. discoideum, but did not affect spore or stalk differentiation in P. pallidum. However, gsk3(−) amoebas entered into encystation under conditions that in wild type favour aggregation and fruiting body formation. The gsk3(−) cells were hypersensitive to osmolytes, which are known to promote encystation, and to cyst-inducing factors that are secreted during starvation. GSK3 was not itself regulated by these factors, but inhibited their effects. CONCLUSIONS: Our data show that GSK3 has a deeply conserved role in controlling cytokinesis, but not spore differentiation in Dictyostelia. Instead, in P. pallidum, one of many Dictyostelia that like their solitary ancestors can still encyst to survive starvation, GSK3 promotes multicellular development into fruiting bodies over unicellular encystment. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13227-018-0101-6) contains supplementary material, which is available to authorized users.